2012
DOI: 10.1136/bjsports-2012-091410
|View full text |Cite
|
Sign up to set email alerts
|

Impact of accelerometer wear time on physical activity data: a NHANES semisimulation data approach

Abstract: These data suggest that using accelerometer wear time criteria of 12 h/day or less may underestimate step count and time spent in various PA levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
77
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(84 citation statements)
references
References 37 publications
5
77
0
Order By: Relevance
“…I found that non-wear time had the greatest impact on estimates of time spent in SB. This is consistent with previous research that demonstrated that shorter wear times resulted in lower estimates of time spent in PA and SB, with the greatest difference seen for SB 320 .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…I found that non-wear time had the greatest impact on estimates of time spent in SB. This is consistent with previous research that demonstrated that shorter wear times resulted in lower estimates of time spent in PA and SB, with the greatest difference seen for SB 320 .…”
Section: Discussionsupporting
confidence: 92%
“…Despite their wide use, inconsistencies in data reduction procedures have been identified that may reduce comparability between studies [317][318][319][320] , and compromise the validity of accelerometer estimates [321][322][323][324][325][326] . It is important to identify and minimise sources of error and bias in data reduction procedures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has further been shown that assessments of an individual's physical activity are fairly accurate when monitored using an activity monitor (pedometer or accelerometer) for approximately 1 week [25]. It has also been reported that wearing an accelerometer leads to increased number of steps [26]. Therefore, we believe that the fact that participants of this study wore accelerometers generated motivation, making their physical activity visible, and self-monitoring led to increase in steps and activity calories.…”
Section: Discussionmentioning
confidence: 54%
“…Despite the importance of high compliance rates, wear time per day usually remains below 24 h in studies measuring PA in children. This leads to arbitrary decisions regarding wear time validation criteria and inclusion criteria for a valid day, which can significantly affect the compliance rates (12), wear time (7), time spent in different PA intensities (13), and differential bias by exclusion of participants with certain characteristics (27). Furthermore, a review by Cain et al (5) highlighted the great diversity of methods and criteria used to process accelerometer-based data in studies investigating PA in children published between 2005 and 2010, which makes comparisons between studies difficult.…”
mentioning
confidence: 99%